BREAST IMAGING USING 3D ELECTRICAL IMPEDENCE TOMOGRAPHY - Prasad, Sachin N.; Houserkova, Dana; Campbell, Jan (Biomedical papers, 2008)
Aim: To determine the diagnostic efficiency of 3D Eletrical Impedance Tomography (EIT) compared to Mammography (MG) and Ultrasonography (USG) in imaging the breast.Materials and Methods: A group of 88 patients presenting with various breast complaints was examined using combined Mammography and Ultrasonography (MG & USG) or either of these modalities alone. The same patients were then examined using the 3D EIT imaging system "MEIK". The findings were then compared. The sensitivity of these modalities for this group of patients were later determined and statistically analysed.Results: Of the total of 88 patients, 59 findings were "suspicious" by any of the 3 modalities alone or by their combination. EIT had a sensitivity of 77.8 % compared to MG with a sensitivity of 83.3 % and USG with a sensitivity of 94.4 % regarding cases of fibrocystic mastitis. For cases involving cysts, EIT had 100 % sensitivity which was the same as that for USG compared to MG with a sensitivity of only 81 %. Among cases of fibroadenoma, EIT had a sensitivity of just 68.8 % compared to MG with a sensitivity of 87.5 % and USG with a sensitivity of 75 %. Finally among cases of carcinoma, EIT had a sensitivity of 75 % compared to the sensitivity of 100 % of MG and USG in our group of patients. The study revealed that there was no overall significant difference in sensitivity between MG-USG (p = 0.219) and MG-EIT (p = 0.779) and USG-EIT (p = 0.169). However, in regard to identifying cysts there was significant difference in the sensitivity of MG compared to USG & EIT suggesting that EIT has a role in these cases.Conclusion: Electrical impedance could be used as an adjunct to Mammography and Ultrasonography for breast cancer detection. However, the differentiation of malignant from benign lesions based on impedance measurements needs further investigation. Multifrequency electrical impedance imaging appears the most promising for detecting breast malignancies but methodological improvements need to be made to realise its potential.
Keywords: Mammography/Ultrasonography/Bio-impedance/3D EIT/Breast Imaging